Bioinspired Adhesion: Multiple Mechanical Gradients are Responsible for the Strong Adhesion of Spider Attachment Hair (Adv. Mater. 37/2020). Issue 37 (15th September 2020) - Flenner, Silja; Schaber, Clemens F.; Krasnov, Igor; Stieglitz, Hergen; Rosenthal, Martin; Burghammer, Manfred; Gorb, Stanislav N.; Müller, Martin
Abstract : Nanostructured adhesive hairs on the feet of spiders are responsible for strong adhesion, enabling the animals to walk vertically and upside down. In article number 2002758, Clemens F. Schaber, Martin Müller, and co‐workers use scanning nanofocus X‐ray scattering under force control to elucidate the mechanism of alignment and consequently strong attachment of the nanostructures to a glass surface. The spider attachment system is a promising model for the development of powerful residue‐free dry adhesives.